Influence of the use of different doses of enzymatic additive on the quality of sorghum silage (Research, Society and Development, 2023)
About the goal of evaluating the effects of the use of additives in sorghum ensilage, an experiment was carried out in which the productive and fermentative parameters and the nutritional quality of the silages were analyzed. The experimental design was completely randomized, with different levels of inclusion of powdered Rovabio® enzymatic additive being tested, constituting the following treatments: 1) Sorghum without inclusion of enzymes (control), 2) Sorghum + 100 g/ton/MV of enzyme, 3) Sorghum + 250 g/ton/MV of enzymes 4) Sorghum + 500 g/ton/MV of enzyme, diluted in 60 ml of distilled water. To measure silage fermentation, pH, dry matter recovery, gas and effluent losses, ammonia nitrogen, buffering power and density were estimated. Bromatological and digestibility parameters were also evaluated. The addition of increasing doses of the enzymatic additive Rovabio® is not positive for all quality parameters of the sorghum silage, as the digestibility of the silage was impaired with any dose of additive.